2- Resolver las siguientes ecuaciones
a) x + 3(x-1)-7 = 6
b) 3x - 12:3+ 2 + 3x - 1) = 13
c) 8:4 + 2(x + 1) - 10:5 + 5 = 9
d) 9-8:2 + 3x - 2x + 1) = 18: 3 - 6:3 + 1
e) (x - 2*6 - 1 + 3x): 2 = 38
19x + 17 + 3(x + 1) = 5*3 + 1
g) 3x + 2-2(2x - 3) = x-2
h) 9x + 14:2 + 5 = 10:2 + 3 + 3*2-1
I) 2(3x - 15) - 4x + 20 = 2
por favor rrrrr
alejocrak73:
plis
Respuestas
Respuesta dada por:
0
Respuesta:
el resultado es 1230 gracias por su servicio
Preguntas similares
hace 3 años
hace 3 años
hace 5 años
hace 7 años
hace 7 años